EVALUATION OF ANTIOXIDANT POTENTIAL OF TWO DAPHNE SPECIES (D. GNIDIOIDES AND D. PONTICA) FROM TURKEY - Sanda, Murad Aydýn; Zengin, Gokhan; Aktumsek, Abdurrahman; Cakmak, Yavuz Selim (Emirates Journal of Food and Agriculture, 2015)
Daphne species have been used traditionally for treatment of several ailments including rheumatism, abscess and diarrhoea. Purpose of present study was to evaluate antioxidant activities of methanol and water extracts of Daphne parts (roots, stems and leaves). Different experimental models including phosphomolydenum, DPPH, β-carotene/linoleic acid, ferric and cupric reducing power assays were performed to characterize the antioxidant potentials of the extracts. Folin-Ciocalteu and AlCl3 methods were also used to quantify total phenolic and flavonoid content, respectively. D. pontica leaf extract showed high phenolic contents (123.09 mgGAEg-1 in methanol and 146.94 mgGAEg-1 in water extract) therefore has the strongest antioxidant potential. Present study showed that Daphne extracts (D. gnidioides and D. pontica) can be considered as good sources of natural antioxidants for medicinal and food applications.